ANALYSIS OF THE CATEGORY SHIFT OF NOUN PHRASES IN TRANSLATION OF THE QUEEN SWALLOW’S GIFT - Rini, Yulan Puspita (Universitas Islam Negeri Raden Intan Lampung, 2015)
In doing the process of translating, translator does several steps in delivering the meaning of the source text into target text. The goal of process of translating is to find equivalent term of source text in the target text. There is no exact linguistic system between two languages. Because of this difference, equivalence is quite hard to be achieved in the target language. As the consequence, sometimes, there is a shift in the target text. The This research is analyzing the noun phrases in term of what kind of category shift done by the translator in translating the noun phrases?